2020
DOI: 10.1016/j.tifs.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The next protein transition

Abstract: A B S T R A C TBackground: Meeting the UN Sustainable Development Goals requires a relatively rapid transition towards a circular economy. Therefore, a multidisciplinary perspective is required to sketch why a transition from diets based primarily on animal proteins towards diets based primarily on plant proteins products is extremely urgent for both food security and sustainability. Scope and approach: This review starts out by identifying ecological, economic and social aspects of sustainable food consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(163 citation statements)
references
References 62 publications
(76 reference statements)
1
136
0
1
Order By: Relevance
“…A number of studies conclude that increases in animal protein production and consumption are unsustainable, contributing to degraded natural systems, biodiversity losses and climate change [1][2][3][4][5]. These changes are also implicated in an array of human health issues [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies conclude that increases in animal protein production and consumption are unsustainable, contributing to degraded natural systems, biodiversity losses and climate change [1][2][3][4][5]. These changes are also implicated in an array of human health issues [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The production of animal-based foods such as meat and dairy products is identified as a key driver of land degradation, loss of biodiversity and climate change, which threatens the safe operating space of the "planetary boundaries" (Clark & Tilman, 2017;Rockstrom et al, 2009;Willett et al, 2019). In contrast, plantbased foods are usually more efficient for converting natural resources into calories and nutrients for human consumption (Clark & Tilman, 2017;Aiking & de Boer, 2018;Lacroix, 2018;Poore & Nemecek, 2018). A shift toward more plant-based diets can also generate substantial gains for public health, especially when these diets are rich in foods such as nuts, fruits, vegetables, and legumes, due to increased exposure to healthprotective factors and decreased exposure to harmful factors such as saturated fats (Springmann et al, 2016;Tilman & Clark, 2014;Westhoek et al, 2014;Willett et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For some foods added to the diet from a health perspective (such as dairy, fish, nuts and fruits), a higher consumption may increase the environmental impact. The overarching principles such as to lower animal-based and increase plant-based foods have been put forward as a proxy for healthy [40] and sustainable diets [93]. These principles may especially serve to lower the disruption of the nitrogen cycle as animal products have the largest nitrogen losses along the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Combining both perspectives, starting from working examples, and combining several types of policy instruments is the most promising way forward towards integrated food policies. Public health policies showed that the most effective policies include a mix of policies involving market-based instruments, that suit aspects of public health and the environment, although more research may be needed [93].…”
Section: Practical Implicationsmentioning
confidence: 99%